Urban infrastructure in Latin America and the Caribbean: Public policy priorities - Laura Jaitman (Latin American Economic Review, 2015)
Latin America and the Caribbean is the most urbanized region in the developing world. Its urbanization rate of almost 80 % is comparable to that of high-income countries. However, cities in the region are struggling to provide the infrastructure needed for their millions of residents to enjoy a decent quality of life. This paper focuses on analyzing three aspects of this challenge. First, it identifies the main problems in housing and transport infrastructure in the region. Second, it examines the effect of past interventions to improve the living standards of the urban poor. And third, it analyzes the relationship between housing supply and transport networks, two connected topics that shape the region's spatial urban patterns.
Keywords: O18; R0; R3; R4; 330; Urban infrastructure; Transport; Slums; Housing; Land titling; Impact evaluation